Mokit Prototype Design Indonesian Traditional House (Series 1: Joglo House) - Pertiwi, Elianna Gerda; Wahyudi, Luqman; Fauziah, Emmareta (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Many factors affect the existence of the current Joglo house. One of them is the lack of public understanding of the function of space and the architectural form of the Joglo house. Lack of understanding is a factor causing shifting cultural values. Therefore, this study aims to build this understanding by designing a product model of the Joglo House raft (mokit) as an interactive learning medium about building structures. A qualitative method is used with a design thinking process (design mindset) to achieve the research objectives. Design thinking consists of 5 stages: first, data collection (empathy); at this stage, interviews, observations, and surveys are carried out on students, architecture, and interior lecturers. Second, the definition stage is to determine the requirements and needs of the research. Third, the idea stage develops ideas and various alternative designs in the Mokit design by conducting FGD and brainstorming. Fourth, the prototype stage or making prototypes, and finally, the test or trial stage. However, this research is limited to the prototyping process, so that the final result of the research is a prototype of the Joglo traditional house mokit.